Financial stability index and business cycle in Malaysia - Koong, Seow Shin; Law, Siong Hook (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
Financial sector plays an important part in a system of economy, in which the intermediation function of financial intermediaries is of particular important in channeling funds. However, it exposes to potential financial risks that might lead to economic crisis. This study develops a financial conditions index and relates its explanatory power on Malaysian business cycle. A wide array of financial indicators is used to construct the index using dynamic factor model. The empirical analyses demonstrate that the constructed index appears to have explanatory power on the business cycle. Testing the forecast rationality, it is found that the business cycle forecast is rational and there is incremental information content at 3-months horizon. Moreover, the changes of the index were found to lead the movement in business cycle. Hence, the constructed index can act as a leading indicator in explaining and forecasting Malaysian business cycle as well as an early warning for policymakers to make appropriate and timely policy actions.